(untitled) (Research, Society and Development, 2023)
During the COVID-19 pandemic, self-medication intensified due to several factors, such as the ease of obtaining medicines without a prescription, difficulty in accessing health services and the wide media dissemination of over-the-counter drugs for the population. In view of this, the present study aimed to evaluate the prevalence and factors associated with self-medication in the COVID-19 pandemic. Data collection occurred through the application of a questionnaire on the practice of self-medication during the COVID-19 pandemic. The online questionnaire was sent to individuals aged 18 years or older, residents of the metropolitan region of Belém. Thus, a total of 273 valid responses were obtained. From the evaluation of the data, it was noted the prevalence of the practice in females, in young adults and individuals without higher education. In addition, among the drugs used, non-opioid analgesics and Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) stand out. With these and other data in hand, public policies can be devised to minimize the practice of uncontrolled self-medication, avoiding the appearance of adverse effects due to the irrational use of drugs, especially during situations of great risk to public health.